Law and regulation of community interest companies - Bishop, Richard C. (London : Bloomsbury Professional, 2022)
This new title provides a full analysis of the legislative and regulatory background of community interest companies and is a guide to all six CIC precedents. Armed with this text any solicitor, barrister or accountant will have the tools to confidently advise clients on the legislative and regulatory background of CICs. This text would also suit community bodies or individuals who wish to set up a social enterprise using the CIC structure, in particular, sports clubs or voluntary groups..
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Charity law -- United Kingdom; Company law -- United Kingdom; Law; Corporation law; Great Britain